The Relatioship Between Medication Adherence of Stroke Patients and Recurrent Stroke Incidance At Siti Hajar Islamic Hospitas Mataram - Rahma, Baiq Suyatmin; Nurhidayati, Nurhidayati; Mahacita Andanalusia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Stroke was the second leading cause of death and a major cause of disability worldwide. One of primary challenges in stroke management was patient adherence to treatment, which significantly influences risk of recurrent stroke. This study aimed to analyze relationship between medication adherence among stroke subjects, were stroke patients at Siti Hajar Islamic Hospital, Mataram. This research employed an analytical observational study with a cross-sectional approach. Data were collected through interviews, a medication adherence questionnaire, and medical records. The Spearman test was used to analyze the relationship between medication adherence and the occurrence of recurrent stroke. The study showed that patient levels of adherence to stroke medication varied, with a portion exhibiting low to moderate adherence. Spearman correlation analysis indicated no significant relationship between medication adherence and recurrent stroke events (p value= 0.359; r= 0.111). The p-value greater than 0.05 suggested that the relationship between the two variables was not statistically significant, although a weak positive correlation was observed. In conclusion, there was no statistically significant association between medication adherence and recurrent stroke in patients at Siti Hajar Islamic Hospital Matarm. These findings suggested that medication adherence might not be only factor influencing stroke recurrence, and further evaluation of other contributing factors is necessary.